Teams a competency-based approach - Ramirez, Consuelo (Routledge, Taylor & Francis Group, 2014)
Learning to work effectively and efficiently in a group is an important part of learning to be a substantive contributor in today’s business environment. Teams: A Competency Based Approach provides a solid coverage of the underlying theory of teamwork, complemented by examples, to help students learn and practice the competencies that will allow them to take advantage of team-building opportunities. This book helps readers to systematically identify, analyze and manage issues that arise as a result of teamwork by emphasizing four important objectives for successful team-members: Recognizing opportunities for accomplishing goals within a team context ; Appreciating other individuals' attributes in a group setting ; Analyzing the types of environments in which teamwork is most advantageous ; Identifying and building the necessary competencies to leverage successful group experiences. With exercises and activities designed to allow readers to engage with the material and build specific team-oriented competencies, this book offers undergraduate students interested in management, team building, and human resource training the tools needed for successful group experiences.